Unleashing recyclates for enhanced mechanical and durability performances of ternary blended concrete - Solomon Oyebisi; Mohammed Alquraish (PLoS ONE, 2025)
The recycling of waste materials as environmentally friendly cement alternatives to lessen the impact of CO 2 emissions and safeguard natural resources associated with cement manufacturing cannot be over-emphasized. This study investigates the effects of recycled waste materials such as shea nutshell ash and ground oyster seashell as Portland limestone cement substitutes on the mechanical, durability, and sustainability performances of ternary blended concrete. Shea nutshell ash and ground oyster seashell were partially used as cement replacement at 5–15 wt. % and tested for mechanical properties after 3–120 curing ages. Chemical resistances and drying shrinkage were conducted as durability performance after 120 and 1–120 curing ages. The results revealed higher compressive, flexural, and split tensile strengths at later ages, with about a 3% increase at 10 wt. % substitution after 90 curing ages than the control concrete. Ternary blended concrete samples, at 5–10 wt. % of shea nutshell ash and ground oyster seashell replacement levels, resulted in improved acidic, sulfate, and drying shrinkage resistances by 11–40%, 12–53%, and 9–34%, compared to the control samples. Ultimately, this research recommends an optimum of 10 wt. % shea nutshell ash and ground oyster seashell as cement alternatives, enhancing mechanical durability properties of ternary blended concrete.